1982
DOI: 10.2165/00003088-198207020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Antiarrhythmic Agents

Abstract: Therapeutic drug monitoring has come of age in clinical medicine and, in particular, its use with antiarrhythmic agents has flourished. The classic indications for the use of therapeutic drug monitoring are commonly encountered with antiarrhythmic drug use. Most of the currently available allliarrhythmics have a narrow therapeutic index, necessitating car~ful dose titration. The ~rfectiveness of these agents in clinical use isfrequent(v d([ficultlo determine as a result of marked variability in arrhythmia freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 117 publications
1
8
0
Order By: Relevance
“…From the above data, the therapeutic range of lignocaine serum concentrations has been accepted as 2.0 to 5 mg/L (Brown and Shand, 1982;Follath 11 et aI., 1983). Although it is clear that most patients n~ed concentrations > 2.0 mg/L for a salutary response, one should remember that efficacy may require concentrations higher than the usual upper limit if toxicity can be avoided.…”
Section: Correlation Of Serum Concentrations With Clinical Responsementioning
confidence: 99%
“…From the above data, the therapeutic range of lignocaine serum concentrations has been accepted as 2.0 to 5 mg/L (Brown and Shand, 1982;Follath 11 et aI., 1983). Although it is clear that most patients n~ed concentrations > 2.0 mg/L for a salutary response, one should remember that efficacy may require concentrations higher than the usual upper limit if toxicity can be avoided.…”
Section: Correlation Of Serum Concentrations With Clinical Responsementioning
confidence: 99%
“…The commonly accepted therapeutic plasma concentration range for procainamide is 4 to 10 J.Lg/ ml (Brown and Shand, 1982). However, one study has shown that plasma procainamide concentrations as high as 33 J.Lgjml may be required to suppress recurrent ventricular tachycardia in some patients and can be tolerated well (Greenspan et aI., 1980).…”
Section: J Pharrnacokinetic Propertiesmentioning
confidence: 99%
“…Rapid acetylators achieve plasma concentrations that may be therapeutic within 24 hours, but these patients also have lower plasma concentrations of procainamide (Crawford et a\., 1982;Lima et a\., 1978). The contribution of NAPA to the therapeutic effect of a given dose of procainamide is therefore varied and difficult to quantitate (Brown and Shand, 1982). There are currently no data demonstrating that a change in procainamide dose during the first 24 hours of therapy is required based on a patient's acetylator status.…”
Section: J Pharrnacokinetic Propertiesmentioning
confidence: 99%
“…The therapeutic plasma concentration range has not been definitely established, but recent reviews of the literature point to lower and upper limits of approximately 2-3 mg/l (6-9 umol 1) and 5-6 mg,l (15-18 ,Amol l), respec-tively (Brown & Shand, 1982;Garfein, 1982;Kates, 1980). Intravenous dosing schedules for the treatment of ventricular arrhythmias associated with acute myocardial infarction are designed with the aim of rapidly attaining therapeutic plasma concentrations.…”
Section: Introductionmentioning
confidence: 99%